A battery separator and preparation method thereof and secondary battery
By coating the porous substrate layer of the battery separator with inorganic particles and organic matter, the problem of poor shrinkage and wettability of the polyolefin battery separator at high temperature is solved, the breakdown voltage resistance and peel strength are improved, and the heat resistance and stability of the battery separator are enhanced.
Patent Information
- Application Number
- CN202411624469.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-14
AI Technical Summary
The existing polyolefin battery separators are prone to shrink at high temperatures, have poor wettability of the electrolyte, and the introduction of functional materials leads to poor insulation and stability, and insufficient breakdown voltage resistance and peel strength.
The porous substrate layer is combined with a coating. The coating consists of inorganic particles and organic matter. By regulating the true density of inorganic particles, the density of organic matter, the thickness of the coating and the breathability increase value, it ensures that the peel strength between the coating and the porous substrate layer and the breakdown voltage of the battery separator meet the specified requirements.
It improves the breakdown voltage resistance and peel strength of the battery separator, enhances the heat resistance and stability of the battery separator, reduces the risk of short circuit, and improves the safety and cycle life of the secondary battery.
Smart Images

Figure CN119153893B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a battery separator and a preparation method thereof, and a secondary battery. Background Art
[0002] With the continuous development of society, energy and environmental issues have become increasingly hot topics. Secondary batteries, such as lithium-ion batteries, as a new type of energy storage device, have the advantages of high charge and discharge voltage platform, long cycle life, no pollution, and low self-discharge. Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, electrolyte, and separator. Among them, the battery separator is one of the key components of lithium-ion batteries. Its main functions are: (1) prevent the positive electrode and the negative electrode from directly contacting and short-circuiting; (2) absorb electrolyte and provide a channel for the migration of lithium ions.
[0003] In the past few decades, polyolefin battery separators have been widely used in lithium-ion batteries due to their excellent chemical stability, good mechanical strength and low price. However, polyolefin battery separators still have many defects, such as poor wettability of electrolytes and large shrinkage at high temperatures. In order to solve the above problems, the prior art usually coats one or more layers of functional materials on the porous substrate layer of the polyolefin battery separator. However, the introduction of functional materials also makes the insulation and stability of the battery separator after coating worse, resulting in a decrease in the ability of the battery separator to withstand breakdown voltage. In addition, if the bonding force between the functional material coating and the porous substrate layer is low, there will also be a risk of peeling between the coating and the porous substrate layer, affecting the performance of the battery separator. Summary of the invention
[0004] The purpose of this application is to provide a battery separator with strong anti-breakdown voltage capability and high anti-peel strength, a preparation method thereof, and a secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, and the coating surface density of the coating is C g / m 2 , the coating thickness is H μm, the permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1g / cm 3 , the density of organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of inorganic particles is W1, and the mass percentage of organic matter is W 2i ,satisfy: ,in, , n is the number of types of organic matter; the peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV.
[0006] In some embodiments of the present application, the mass percentage of inorganic particles satisfies: 82%≤W1≤97%, and the mass percentage of organic matter satisfies: .
[0007] In some embodiments of the present application, the thickness of the coating satisfies: 0.5≤H≤8, and the coating surface density of the coating satisfies: 1≤C≤10.
[0008] In some embodiments of the present application, the bulk density of the inorganic particles is D3 g / cm 3 , inorganic particles satisfy: 2.3≤D1-D3≤3.1.
[0009] In some embodiments of the present application, the particle size PSD (Particle Size Distribution) of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm, wherein,
[0010] .
[0011] In some embodiments of the present application, the surface hydroxyl groups of the inorganic particles account for 0 to 0.06% by mass.
[0012] In some embodiments of the present application, the inorganic particles are selected from at least one of silica, alumina, magnesia, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, barium fluoride or barium titanate.
[0013] In some embodiments of the present application, the organic matter includes a first organic matter, and the first organic matter is selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers or acrylamide and its derivative copolymers. Optionally, the first organic matter can be one of polyvinylidene fluoride or acrylic resin or a combination thereof. Based on the mass of the coating, the mass percentage of the first organic matter is W 21 , meet: 3%≤W 21 ≤10%.
[0014] In some embodiments of the present application, the glass transition temperature (T g ) is -40°C to 100°C, and the temperature range of the glass transition temperature is ≤12°C, wherein the temperature range of the glass transition temperature is the difference between the end point and the starting point of the glass transition temperature.
[0015] In some embodiments of the present application, the swelling ratio of the first organic matter in the electrolyte is 40% to 150%.
[0016] In some embodiments of the present application, the shear retention rate of the first organic matter is 0 to 0.08%.
[0017] In some embodiments of the present application, the peel strength between the coating layer and the porous substrate layer is ≥39 gf / 15 mm, and the breakdown voltage of the battery separator is ≥1.70 kV.
[0018] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry comprising inorganic particles and organic matter, wherein the organic matter comprises a first organic matter; (3) coating the coating slurry on at least one surface of the porous substrate layer, drying the coating slurry, and obtaining a battery separator comprising a coating.
[0019] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, and 40-70 parts of a solvent.
[0020] In some embodiments of the present application, when the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3 L / min to 9 L / min, and the temperature of the coating slurry is 18° C. to 30° C.
[0021] In some embodiments of the present application, the pH of the coating slurry is 7 to 10, the viscosity is 5 to 200 mPa·s, and the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm.
[0022] In some embodiments of the present application, during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm.
[0023] In some embodiments of the present application, the absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 20° C. to 65° C.
[0024] The third aspect of the present application provides a secondary battery, which includes the battery separator provided in the first aspect of the present application or the battery separator prepared by the preparation method provided in the second aspect.
[0025] Beneficial effects of this application:
[0026] The present application provides a battery separator and a preparation method thereof and a secondary battery, wherein the peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV. The battery separator of the present application has good anti-breakdown voltage capability and high peel strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0028] Figure 1 This is a schematic diagram of the structure of a battery separator along its thickness direction according to one embodiment of the present application.
[0029] Reference numerals: battery separator 10 , porous substrate layer 11 , coating layer 12 . DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0031] The first aspect of the present application provides a battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, and the coating surface density of the coating is C g / m 2 , the coating thickness is H μm, the permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1g / cm 3 , the density of organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of inorganic particles is W1, and the mass percentage of organic matter is W 2i ,satisfy: ,in, , n is the number of organic species. For example, The value of can be 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of these values. The peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV. In this application, the permeability increase of the battery separator is the difference between the permeability of the battery separator and the permeability of the porous substrate layer. The true density refers to the actual volume of solid matter within the volume of the material in an absolutely dense state, excluding internal pores or gaps between particles. When the coating includes two or more organic substances, D in A 2i ×W 2iIt is the product of the density of each organic matter and its mass percentage.
[0032] The inventors of the present application have discovered that in the preparation of battery separators, the properties of the materials determine the affinity between the battery separator and the electrolyte, the liquid absorption and retention rate, and the ion transfer efficiency. By selecting the true density of the inorganic particles and the density of the organic matter in the coating, the inorganic particles and organic matter that are beneficial to improving the affinity between the battery separator and the electrolyte, the liquid absorption and retention rate, and the ion transfer efficiency are screened out and applied to the battery separator. The improvement of the above-mentioned properties of the battery separator can improve its ability to resist breakdown voltage and peel strength; at the same time, by regulating the mass percentage of the inorganic particles and organic matter in the coating, the increased permeability of the battery separator, the coating surface density, and the coating thickness, the porosity, pore size, and pore size distribution of the battery separator can be improved to further improve the ability to resist breakdown voltage and peel strength of the battery separator; further, by regulating the above-mentioned parameters of the battery separator to meet , the anti-breakdown voltage capability and peel strength of the battery separator can be further improved, so that the peel strength between the coating and the porous substrate layer is ≥20gf / 15mm, and the breakdown voltage of the battery separator is ≥0.5kV. The above battery separator is applied to secondary batteries, which can reduce the short circuit rate of secondary batteries, improve safety, reduce the internal resistance of the battery to improve its charge and discharge efficiency, increase energy density, and improve cycle life.
[0033] when If the value of is too small, for example, less than 2, the gap between the inorganic particles and the organic matter is too large. Although the transmission rate of lithium ions can be improved to a certain extent, the gap formed also significantly increases the electron passing rate, resulting in a decrease in the resistance of the battery separator, a decrease in the breakdown voltage, and a decrease in the ability to resist breakdown voltage, which affects the safety performance of the secondary battery. When the value of is too large, for example greater than 10, the inorganic particles in the coating are unevenly distributed, resulting in excessive resistance to lithium ions during migration, which reduces the passage rate of lithium ions, and the organic matter partially penetrates into the micropores of the porous substrate layer to form electron channels in the micropores of the porous substrate layer. The breakdown voltage of the battery separator is reduced, and the anti-breakdown voltage capability is reduced, resulting in an increase in the internal resistance of the secondary battery and a deterioration in the cycle performance.
[0034] In some embodiments, the peel strength between the coating layer and the porous substrate layer is 20 gf / 15 mm to 500 gf / 15 mm. For example, the peel strength between the coating layer and the porous substrate layer can be 20 gf / 15 mm, 24 gf / 15 mm, 28 gf / 15 mm, 30 gf / 15 mm, 35 gf / 15 mm, 39 gf / 15 mm, 40 gf / 15 mm, 42 gf / 15 mm, 45 gf / 15 mm, 48 gf / 15 mm, 50 gf / 15 mm, 52 gf / 15 mm, 55 gf / 15 mm, gf / 15mm, 60gf / 15mm, 80gf / 15mm, 100gf / 15mm, 130gf / 15mm, 170gf / 15mm, 200gf / 15mm, 250gf / 15mm, 300gf / 15mm, 350gf / 15mm, 400gf / 15mm, 450gf / 15mm, 500gf / 15mm or a range consisting of any two of them.
[0035] In some embodiments, the breakdown voltage of the battery separator is 0.5 kV to 8 kV. For example, the breakdown voltage of the battery separator can be 0.5 kV, 0.7 kV, 0.9 kV, 1 kV, 1.2 kV, 1.32 kV, 1.35 kV, 1.4 kV, 1.5 kV, 1.6 kV, 1.65 kV, 1.7 kV, 1.75 kV, 1.79 kV, 1.8 kV, 1.83 kV, 1.85 kV, 1.88 kV, 1.89 kV, 1.9 kV, 1.91 kV, 1.95 kV, 2 kV, 2.5 kV, 3 kV, 3.5 kV, 4 kV, 4.5 kV, 5 kV, 6 kV, 7 kV, 8 kV, or a range consisting of any two of the values.
[0036] For ease of understanding, in this application, the length direction of the battery separator itself is defined as X, and the thickness direction is defined as Y. The battery separator usually has a long side and a short side, and the length direction is the extension direction of the long side of the battery separator. It should be understood that the above definition of direction is for the purpose of convenient description of this application. Figure 1 As shown, the battery separator 10 includes a porous substrate layer 11 and coating layers 12 respectively disposed on two surfaces of the porous substrate layer 11 .
[0037] In some embodiments of the present application, the mass percentage of inorganic particles satisfies: 82% ≤ W1 ≤ 97%. For example, the value of W1 can be 82%, 85%, 87%, 90%, 92%, 92.5%, 94%, 94.4%, 95%, 95.2%, 97%, or a range consisting of any two of these values. By regulating the value of W1 within the above range, it is beneficial to improve the heat resistance of the battery separator, and at the same time, the coating and the porous substrate layer have a high peel strength, which is beneficial to improve the anti-breakdown voltage capability and peel strength of the battery separator.
[0038] In some embodiments of the present application, the mass percentage of organic matter satisfies: .For example, The value of can be 3%, 4%, 4.9%, 5%, 5.7%, 6%, 7%, 7.5%, 9%, 11%, 13%, 15%, 18% or a range consisting of any two of these values. By adjusting the mass percentage of organic matter to meet the above conditions, the inorganic particles can have good dispersibility in the coating slurry, which is conducive to preparing a coating with uniform distribution of each component, so that the battery separator has good heat resistance, which is conducive to improving the anti-breakdown voltage capability and peel strength of the battery separator.
[0039] In some embodiments of the present application, the thickness of the coating satisfies: 0.5≤H≤8. For example, the value of H can be 0.5, 1, 1.9, 2, 2.1, 2.2, 3, 5, 5.2, 6, 7, 7.1, 8 or a range consisting of any two of these values. By regulating the value of the thickness H of the coating within the above range, it is beneficial to improve the wettability of the electrolyte to the battery separator, improve the peel strength between the coating and the porous substrate layer and the heat resistance of the battery separator, and improve the anti-breakdown voltage capability and peel strength of the battery separator. It is also beneficial to improve its safety performance and energy density when applied to secondary batteries.
[0040] In the present application, when a coating is provided on only one side of a battery separator, the thickness of the coating refers to the thickness of the coating on that single side; when a coating is provided on both sides of a battery separator, the thickness of the coating refers to the sum of the thicknesses of the coatings on both sides.
[0041] In some embodiments of the present application, the coating surface density of the coating satisfies: 1≤C≤10. For example, the value of C can be 1, 1.5, 2, 2.5, 2.8, 2.91, 2.96, 3, 3.11, 3.21, 3.5, 4, 4.5, 5, 6, 7, 8, 9, 10 or a range consisting of any two of the values. By regulating the coating surface density C of the coating within the above range, it is beneficial to improve the wettability of the electrolyte to the battery separator, improve the peel strength between the coating and the porous substrate layer and the heat resistance of the battery separator, and improve the anti-breakdown voltage capability and peel strength of the battery separator. It is also beneficial to improve its safety performance and energy density when applied to secondary batteries.
[0042] In the present application, when a coating is provided on only one side of the battery separator, the coating surface density of the coating refers to the single-sided coating surface density of the coating; when a coating is provided on both sides of the battery separator, the coating surface density of the coating refers to the sum of the coating surface densities on both sides of the coating.
[0043] In some embodiments, the increased air permeability of the battery separator satisfies: 10≤P≤30. For example, the value of P can be 10, 11, 12, 13, 15, 17, 18, 20, 22, 25, 28, 30, or a range consisting of any two of these values. By regulating the increased air permeability P of the battery separator within the above range, it is beneficial to improve the ion transmission efficiency while improving the breakdown voltage capability and peel strength of the battery separator.
[0044] In some embodiments, the true density of the inorganic particles satisfies: 2≤D1≤5. For example, the value of D1 can be 2, 2.5, 3, 3.04, 3.5, 3.91, 4, 4.5, 5, or a range consisting of any two of these values.
[0045] In some embodiments, the density of the organic matter satisfies: 0.9≤D 2i ≤3. For example, D 2i The value of can be 0.9, 1, 1.02, 1.15, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3 or a range consisting of any two of them.
[0046] In some embodiments of the present application, the bulk density of the inorganic particles is D3 g / cm 3, the inorganic particles satisfy: 2.3≤D1-D3≤3.1. For example, the value of D1-D3 can be 2.3, 2.4, 2.5, 2.6, 2.62, 2.7, 2.8, 2.9, 2.98, 3.0, 3.1 or a range consisting of any two of the values. By regulating the value of D1-D3 of the inorganic particles within the above range, the cohesion between the inorganic particles can be improved, and the organic matter in the coating can be better compatible, which is beneficial to the dispersion of the inorganic particles in the solvent, improves the stability and uniformity of the coating slurry, and prolongs the storage time of the coating slurry. At the same time, it can also maintain a good morphology during the transportation and high-speed coating of the coating slurry, improves the density of the coating after coating and the distribution of organic materials in the thickness direction of the coating, reduces the distribution of organic materials between inorganic particles, and makes the organic materials more distributed at the contact position between the coating and the porous substrate layer, and improves the peel strength between the coating and the porous substrate layer, which is beneficial to improve the anti-breakdown voltage capability and peel strength of the battery separator. In this application, loose packed density refers to the bulk density measured after the powder freely fills a standard container under specified conditions, that is, the mass per unit volume of the powder when loosely packed.
[0047] In some embodiments, the bulk density of the inorganic particles satisfies: 0.2≤D3≤1.2. For example, the value of D3 can be 0.2, 0.3, 0.4, 0.42, 0.5, 0.6, 0.7, 0.8, 0.9, 0.93, 1.0, 1.1, 1.2, or a range consisting of any two of these values.
[0048] In some embodiments of the present application, the particle size distribution PSD of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm. For example, the value of PSD may be 0.38 μm, 0.40 μm, 0.50 μm, 0.51 μm, 0.60 μm, 0.61 μm, 0.62 μm, 0.63 μm, or a range consisting of any two of the values, wherein,
[0049] .
[0050] By regulating the PSD of the inorganic particles within the above range, the inorganic particles are evenly distributed, so that the coating surface of the battery separator is smooth, which is beneficial to improving the breakdown voltage resistance and peeling strength of the battery separator.
[0051] In some embodiments of the present application, the surface hydroxyl mass of the inorganic particles accounts for 0 to 0.06%, preferably 0 to 0.04%. For example, the surface hydroxyl mass of the inorganic particles can be 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06% or a range composed of any two of the numerical values. By regulating the surface hydroxyl mass of the inorganic particles within the above range, it is beneficial to disperse the inorganic particles in the solvent, and after the organic matter is added, it can reduce the reaction with it, which is more conducive to the coating of the inorganic particles by the organic matter, improves the stability of the coating slurry, and makes the distribution of the components of the prepared coating more uniform, which is beneficial to improve the anti-breakdown voltage capability and peel strength of the battery separator.
[0052] In this application, the surface hydroxyl mass ratio of the inorganic particles can be obtained by the following test method:
[0053] (1) Preparation of NaCl solution: weigh 400 g of NaCl into a 2 L beaker, add 1.75 L of water to dissolve, adjust the pH to 3.0 ± 0.1 with hydrochloric acid solution, and take 150 ml of the above NaCl solution;
[0054] (2) Preparation of sodium hydroxide standard solution: c(NaOH) = 0.1 mol / L, according to GB / T 601-2016 Chapter 4 4.1 Preparation and calibration of sodium hydroxide standard titration solution;
[0055] (3) Blank sample addition: titrate with NaOH standard solution at a rate of 20 seconds / drop. When the pH value of the solution reaches 4.0±0.1, the scale value at this time is recorded as V1; continue to titrate until the pH reaches 9.0±0.1. When the pH value of the solution reaches 8.0, reduce the titration speed and add half a drop at 20 seconds. When the pH value changes less than 0.02 within 10 seconds, record the burette scale V2 and calculate the volume of sodium hydroxide solution consumed during the period from pH 4.0 to 9.0 V 空白 =V2-V1;
[0056] (4) Preparation of sample solution: Weigh the inorganic particle sample m after drying at 105°C for 2 h using an analytical balance. 样品 Put 1.5g (accurate to 1mg) in a 250ml beaker, add 150mL of sodium chloride solution, put in a stirrer and stir evenly in a magnetic stirrer, keep the temperature at 25±0.5℃ and wait for titration;
[0057] (5) Sample titration: titrate the inorganic particle sample solution at a rate of 3-4 drops per second. When the pH value reaches the end point, slow down the titration rate and record and calculate the volume V of the sodium hydroxide standard solution consumed when the solution pH changes from 4.0 to 9.0. NaOH ;
[0058] (6) Calculation of surface hydroxyl mass ratio: w(OH)=(V NaOH -V 空白 )×c(NaOH)×17.007 / (m 样品 ×1000), where V NaOH 、V 空白 The unit of is mL, the unit of c(NaOH) is mol / L, m 样品 The unit is g.
[0059] In some embodiments of the present application, the inorganic particles are selected from oxide particles such as silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2), titanium oxide (TiO2), calcium oxide (CaO), nitride particles such as boehmite (ALOOH), aluminum nitride (AlN), boron nitride (BN), barium sulfate (BaSO4), calcium fluoride (CaF2), barium fluoride (BaF2) and other insoluble ion crystalline particles, barium titanate (BaTiO3) particles with high dielectric constant and low dielectric loss. The above-mentioned inorganic particles have stable electrochemical properties, have lithium ion transfer capabilities, can conduct lithium ions in the electrolyte, and promote the transmission of lithium ions. The selection of the above-mentioned inorganic particles is also beneficial to improving the heat resistance of the battery separator, and improving the battery separator's anti-breakdown voltage capability and peel strength. Among the above-mentioned inorganic particles, oxide particles are preferred in view of their stability and potential in the electrolyte. In addition, the inorganic particles need to have a high thermal decomposition temperature (decomposition temperature is higher than 500°C) and low water absorption, preferably aluminum oxide, boehmite, magnesium oxide, silicon dioxide, more preferably aluminum oxide, boehmite, silicon dioxide. When two or more inorganic particles are selected, the present application has no particular restrictions on the ratio of the inorganic particles, as long as the purpose of the present application can be achieved.
[0060] In some embodiments, the coating layer may further include at least one of lithium phosphate, lithium titanium phosphate, lithium aluminum titanium phosphate, lithium nitride, lithium carbonate, lithium chloride, lithium sulfide or lithium hexafluorophosphate, based on the above-mentioned inorganic particles. The above-mentioned substances have the ability to transfer lithium ions, which can improve the ability of the coating layer to conduct lithium ions.
[0061] The present application has no particular restrictions on the shape of the inorganic particles, as long as the purpose of the present application can be achieved. For example, the shape of the inorganic particles can be plate-like, flaky, needle-like, columnar, spherical, polyhedral, blocky, etc., and a variety of inorganic particles with the above shapes can also be used in combination. Preferably, the shape of the inorganic particles is selected from a plate-like, blocky, polyhedral, columnar shape containing multiple faces, so as to improve the permeability of ions in the electrolyte in the battery separator.
[0062] In some embodiments, the dielectric constant of the inorganic particles is ≥ 5. When the dielectric constant of the inorganic particles is within the above range, the inorganic particles have stable electrochemical properties and good lithium ion transfer ability, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.
[0063] In some embodiments, the D of the inorganic particles V 50 is 0.01μm to 2μm, and the specific surface area is 0 to 30m 2 / g, preferably 2m 2 / g to 20m 2 / g, more preferably 3m 2 / g to 18m 2 / g. For example, the D V 50 can be 0.01 μm, 0.2 μm, 0.5 μm, 0.7 μm, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm or a range consisting of any two of these values. The specific surface area of the inorganic particles can be 0 m 2 / g, 2m 2 / g, 3m 2 / g, 5m 2 / g, 10m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 25m 2 / g, 30m 2 / g or a range consisting of any two of these values. V 50 and the specific surface area are within the above ranges, which can increase the surface energy of the inorganic particles, improve the wettability of the electrolyte to the battery separator, and can also improve the fluidity of the coating slurry and the cohesion between the inorganic particles, improve the uniformity and stability of the coating slurry, and reduce the risk of uneven coating of the coating slurry due to high-speed shearing during the coating process, which is beneficial to the preparation of a coating with uniform distribution of each component, and improve the permeability of lithium ions in the electrolyte in the battery separator; at the same time, it can also reduce the water content in the battery separator, reduce the side reactions caused by the presence of water, which is beneficial to improve the anti-breakdown voltage capability and peeling strength of the battery separator, and improve the performance of the secondary battery, such as the cycle performance.
[0064] In this application, Dv10 refers to the particle size at which the volume is accumulated by 10% by volume, measured from the small particle size, in the volume-based particle size distribution of the material; Dv25 refers to the particle size at which the volume is accumulated by 25% by volume, measured from the small particle size, in the volume-based particle size distribution of the material; Dv50 refers to the particle size at which the volume is accumulated by 50% by volume, measured from the small particle size, in the volume-based particle size distribution of the material; Dv75 refers to the particle size at which the volume is accumulated by 75% by volume, measured from the small particle size, in the volume-based particle size distribution of the material; and Dv90 refers to the particle size at which the volume is accumulated by 90% by volume, measured from the small particle size, in the volume-based particle size distribution of the material.
[0065] Normally, inorganic particles with different PSD, Dv50, and specific surface area can be obtained by mechanical crushing (such as ball milling). For example, the PSD, Dv50, and specific surface area of inorganic particles can be controlled by adjusting the ball milling time. When other conditions remain unchanged, the ball milling time is extended, and the PSD of the inorganic particles decreases; the ball milling time is shortened, and the PSD of the inorganic particles increases. When other conditions remain unchanged, the ball milling time is extended, and the Dv50 of the inorganic particles decreases; the ball milling time is shortened, and the Dv50 of the inorganic particles increases. When other conditions remain unchanged, the ball milling time is extended, and the specific surface area of the inorganic particles increases; the ball milling time is shortened, and the specific surface area of the inorganic particles decreases. In addition, the particle size distribution of inorganic particles can also be controlled by changing process parameters such as the material-ball ratio in the ball mill.
[0066] In some embodiments of the present application, the organic matter includes a first organic matter, and the first organic matter is selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers or acrylamide and its derivative copolymers; optionally, the first organic matter can be one of polyvinylidene fluoride or acrylic resin or a combination thereof. The above-mentioned first organic matter is a binder, and the selection of the above-mentioned first organic matter can maintain the mechanical strength and flexibility of the porous substrate layer, so that the battery separator has good mechanical properties, reduce the risk of inorganic particles falling off from the porous substrate layer during the secondary battery preparation process (such as the winding process), and improve the peel strength between the coating and the porous substrate layer, thereby helping to improve the anti-breakdown voltage capability and peel strength of the battery separator.
[0067] The first organic compound of the present application has stable electrochemical performance, which is mainly manifested in that, within a voltage range of 1V to 5V, except for the electrode lithium desorption / insertion redox peak, there is no other redox current peak.
[0068] In some embodiments of the present application, the mass percentage of organic matter is W based on the mass of the coating. 2i , meet: 3%≤W 2i ≤18%. For example, W 2iThe value of can be 3%, 4%, 4.1%, 4.9%, 5%, 6%, 6.5%, 7%, 8%, 9%, 10%, 12%, 14%, 15%, 16%, 18% or a range consisting of any two of these values.
[0069] In some embodiments of the present application, based on the mass of the coating, the mass percentage of the first organic matter is W 21 , meet: 3%≤W 21 ≤10%. For example, W 21 The value of can be 3%, 4%, 4.1%, 4.9%, 5%, 6%, 6.5%, 7%, 8%, 9%, 10% or a range consisting of any two of them. 21 When the value is within the above range, the inorganic particles can have good adhesion, reduce the shedding of inorganic particles, improve the peel strength between the coating and the porous substrate layer and the heat resistance of the battery separator, which is beneficial to improve the battery separator's anti-breakdown voltage capability and peel strength.
[0070] In some embodiments of the present application, the swelling degree of the first organic matter in the electrolyte is 40% to 150%. For example, the swelling degree of the first organic matter in the electrolyte can be 40%, 50%, 58%, 60%, 70%, 77%, 80%, 89%, 90%, 100%, 120%, 140%, 150% or a range composed of any two of the numerical values. By regulating the swelling degree of the first organic matter in the electrolyte within the above range, the storage capacity of the battery separator for the electrolyte can be improved, the bite area and bite force of the first organic matter and the inorganic particles and the porous substrate layer can be increased, and the inorganic particles can be reduced during the charge and discharge process of the secondary battery. The falling off of particles, at the same time, reduces the probability of the first organic matter penetrating into the pores in the porous substrate layer, increases the transmission channel of lithium ions, reduces the transmission internal resistance of lithium ions and lithium ion loss, thereby helping to improve the anti-breakdown voltage capability and peeling strength of the battery separator, and improve the performance of the secondary battery, such as cycle performance.
[0071] In some embodiments of the present application, the glass transition temperature of the first organic substance is -40°C to 100°C, and the temperature domain of the glass transition temperature is ≤12°C, wherein the temperature domain of the glass transition temperature is the difference between the end point and the starting point of the glass transition temperature. For example, the glass transition temperature of the first organic substance can be -40°C, -20°C, 0°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or a range consisting of any two of the values, and the temperature domain of the glass transition temperature can be 0°C, 2°C, 4°C, 6°C, 8°C, 10°C, 12°C, or a range consisting of any two of the values. By regulating the glass transition temperature of the first organic matter and the temperature domain of the glass transition temperature within the above-mentioned range, it is beneficial to form a coating with uniform distribution of components during the coating slurry coating and drying process, increase the contact area between the first organic matter and the porous substrate layer, and improve the peel strength between the coating and the porous substrate layer. At the same time, the rigidity of the prepared battery separator can be reduced, and the probability of powder loss of the coating can be reduced during the subsequent preparation process of the secondary battery (such as slitting and winding), which is beneficial to improve the battery separator's anti-breakdown voltage capability and peel strength.
[0072] In some embodiments of the present application, the shear retention rate of the first organic matter is 0 to 0.08%. For example, the shear retention rate of the first organic matter can be 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or a range consisting of any two of these values. In the present application, the shear retention rate refers to placing a first organic matter of mass m1 in a 1000rpm agitator and stirring for 10 minutes, then filtering the first organic matter with a 200-mesh sieve, and the mass of the first organic matter remaining on the filter is m2, then the shear retention rate = m2 / m1×100%. Regulating the shear retention rate of the first organic matter within the above range is beneficial to improving the anti-breakdown voltage capability and peel strength of the battery separator.
[0073] In some embodiments, the organic matter includes a second organic matter, and the second organic matter is a leveling agent. The second organic matter can be a polysaccharide compound, and can be selected from at least one of a natural polymer compound or a cellulose semi-synthetic polymer compound. The selection of the second organic matter can regulate the viscosity of the coating slurry, improve the dispersibility of the inorganic particles in the coating slurry, make the components of the prepared coating uniformly distributed, achieve a better coating effect, and improve the heat resistance of the battery separator, thereby helping to improve the breakdown voltage resistance and peel strength of the battery separator. Considering the improvement of the dispersibility of the inorganic particles, the second organic matter can be selected as a cellulose semi-synthetic polymer compound.
[0074] In some embodiments, based on the mass of the coating, the mass percentage of the second organic matter is W 22, meet: 0%≤W 22 ≤7%. For example, W 22 The value of can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 6.5%, 7% or a range consisting of any two of them. 22 The value of within the above range can improve the heat resistance of the battery separator, and at the same time make the components of the prepared coating evenly distributed, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.
[0075] In some embodiments, the degree of etherification of the cellulose semi-synthetic polymer compound is 0 to 3, optionally 0.5 to 1.2, further optionally 0.5 to 1, and further optionally 0.7 to 1. For example, the degree of etherification of the cellulose semi-synthetic polymer compound can be 0, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.7, 2, 2.2, 2.5, 3 or a range consisting of any two of the values. By regulating the degree of etherification of the cellulose semi-synthetic polymer compound within the above range, it is beneficial to improve the dispersibility of the inorganic particles in the coating slurry, reduce the water content in the battery separator, and reduce the occurrence of side reactions, thereby helping to improve the breakdown voltage resistance and peel strength of the battery separator. In the present application, the degree of etherification refers to the degree of substitution of the hydroxyl groups (3) of each anhydrous glucose unit in cellulose by substituents such as carboxymethyl.
[0076] In some embodiments, the average degree of polymerization of the cellulose semi-synthetic polymer compound is 1200 to 3000, optionally 1400 to 3000, further optionally 1400 to 2500, and particularly optionally 1400 to 1500. For example, the average degree of polymerization of the cellulose semi-synthetic polymer compound can be 1200, 1400, 1450, 1500, 1800, 2000, 2200, 2500, 2800, 3000, or a range consisting of any two of these values. By regulating the average degree of polymerization of the cellulose semi-synthetic polymer compound within the above range, it is beneficial to make the coating slurry have suitable fluidity, improve the stability and uniformity of the coating slurry, achieve a good coating effect, and make the components of the prepared coating evenly distributed, thereby helping to improve the breakdown voltage resistance and peel strength of the battery separator.
[0077] In some embodiments, the cellulose semisynthetic polymer compound may be selected from at least one of carboxymethyl cellulose, methyl cellulose, sodium carboxymethyl cellulose, hydroxyethyl cellulose, or sodium hydroxyethyl cellulose.
[0078] In some embodiments, the second organic material may also be selected from at least one of styrene maleic anhydride, phenolic resin or polyurethane.
[0079] The present application has no particular restrictions on the type of organic matter, as long as the density and mass percentage of the organic matter in the coating are calculated. Within the scope of this application. For example, the organic matter may include at least one of a first organic matter, a second organic matter, a wetting agent or a dispersant, and may also include other organic matters that can be used for coating. In some embodiments, the organic matter in the coating may be a first organic matter; in other embodiments, the organic matter in the coating may be a first organic matter and a second organic matter.
[0080] In some embodiments, the coating includes inorganic particles, a first organic substance and a second organic substance, and may further include a wetting agent and a dispersant. Based on the mass of the coating, the mass percentage of the wetting agent may be 0% to 1%, and the mass percentage of the dispersant may be 0% to 1%. The present application has no particular restrictions on the types of wetting agents and dispersants, as long as the purpose of the present application can be achieved. For example, the wetting agent may be selected from, but not limited to, at least one of polyether-modified polysiloxanes, polysiloxanes, methyl acrylate polymers, polyoxyethylene dodecylphenol ethers, polyoxyethylene carboxylates, polyoxyethylene alkyl ethers, or sodium sulfates of fatty alcohol polyvinyl ethers, and the dispersant may be selected from, but not limited to, at least one of polycarboxylates, ammonium polyacrylates, or polyvinyl alcohols.
[0081] In some embodiments, the thickness of the porous substrate layer is 0.3 μm to 30 μm, preferably 0.5 μm to 20 μm, and more preferably 3 μm to 15 μm. For example, the thickness of the porous substrate layer can be 0.3 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 5.2 μm, 6 μm, 7 μm, 7.1 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any two of the values. By regulating the thickness of the porous substrate layer within the above range, it is beneficial to the permeation and migration of ions in the electrolyte, and it is beneficial to improve the anti-breakdown voltage capability and peel strength of the battery separator. At the same time, it is beneficial to improve its energy density when applied to secondary batteries.
[0082] In some embodiments, the porosity of the porous substrate layer is 10% to 70%, preferably 20% to 60%. For example, the porosity of the porous substrate layer can be 10%, 20%, 30%, 40%, 50%, 60%, 70% or a range consisting of any two of these values. By regulating the porosity of the porous substrate layer within the above range, more transmission channels can be provided for ions, the transmission distance of ions can be shortened, and the ion transmission efficiency can be improved. At the same time, it is also beneficial to absorb and retain the electrolyte, enhance the wettability of the electrolyte to the battery separator, and help improve the anti-breakdown voltage capability and peel strength of the battery separator.
[0083] In some embodiments, the porous substrate layer is selected from a polyolefin substrate, a non-woven fabric substrate or an electrospinning substrate, preferably a polyolefin substrate. The use of the above porous substrate layer is conducive to improving the anti-breakdown voltage capability and peel strength of the battery separator.
[0084] In some embodiments, the polyolefin substrate is selected from any one of single-layer polyethylene, single-layer polypropylene, multi-layer polyethylene and multi-layer polypropylene. From the perspective of film-forming performance, the polyolefin substrate is preferably polyethylene and its copolymers, and can be at least one of ultra-high molecular weight polyethylene, high-density polyethylene and low-density polyethylene. Polyethylene can be obtained by a one-step polymerization method or a multi-step polymerization method. The use of the above-mentioned polyolefin substrate is conducive to further improving the anti-breakdown voltage capability and peel strength of the battery separator.
[0085] In some embodiments, the molecular weight of polyethylene is 300,000 to 5 million, preferably 400,000 to 4 million, and more preferably 500,000 to 3 million. For example, the molecular weight of polyethylene can be 300,000, 400,000, 500,000, 600,000, 800,000, 1 million, 1.5 million, 2 million, 2.4 million, 3 million, 3.5 million, 4 million, 4.5 million, 5 million, or a range consisting of any two of these values.
[0086] In other embodiments, the porous substrate layer can be a polyolefin substrate prepared by mixing a polyolefin having a molecular weight of 300,000 to 800,000 with a polyolefin having a molecular weight of 2 million to 5 million. The use of the above polyolefin substrate is conducive to further improving the anti-breakdown voltage capability and peel strength of the battery separator. In this application, molecular weight refers to the weight average molecular weight.
[0087] In some embodiments, the particle size of the polyethylene is less than or equal to 500 μm. For example, the particle size of the polyethylene can be 250 μm, 300 μm, 400 μm, 500 μm, or a range consisting of any two of these values. In this application, the particle size of the polyethylene refers to the average particle size (Dv50) of the polyethylene masterbatch used to prepare the porous substrate layer.
[0088] In this application, the true density of inorganic particles can be tested by the gas volume method, which is specifically as follows: placing the inorganic particle sample in a true density tester, gradually increasing the pressure to allow the gas to enter the pores of the sample, and then recording the pressure change to determine the volume of the sample, thereby calculating the true density of the inorganic particles. The true density of inorganic particles can also be tested by the immersion method, which is specifically as follows: immersing the inorganic particle powder to be tested in an immersion liquid that wets it but does not dissolve it, vacuuming to remove bubbles, and then measuring the volume of liquid discharged from the powder sample from a container of known capacity, thereby calculating the true density of the inorganic particles. The test of the bulk density of inorganic particles can refer to GB / T 31057.1-2014 "Testing of Physical Properties of Granular Materials Part 1: Test of Bulk Density". The test of the density of organic matter can refer to GB / T 611-2021 "General Method for Determination of Density of Chemical Reagents". The glass transition temperature of organic matter can be tested by differential scanning calorimetry (DSC).
[0089] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry comprising inorganic particles and organic matter, wherein the organic matter comprises a first organic matter; (3) coating the coating slurry on at least one (for example, one or two) surface of the porous substrate layer, and drying the coating slurry to obtain a battery separator comprising a coating.
[0090] The present application has no particular restrictions on the production and preparation process of the porous substrate layer, as long as the purpose of the present application can be achieved. For example, the porous substrate layer can be prepared by dry uniaxial stretching, biaxial synchronous or asynchronous stretching, or wet biaxial synchronous or asynchronous stretching, preferably by wet biaxial synchronous or asynchronous stretching.
[0091] The present application has no particular restrictions on the production and preparation process of the inorganic particles, as long as the purpose of the present application can be achieved. For example, in the preparation process of the inorganic particles, the steam foam inlet temperature can be 280°C to 300°C, the steam outlet temperature can be 115°C to 125°C, and the steam foam time can be 5min to 20min.
[0092] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-30 parts of organic matter and 40-70 parts of solvent.
[0093] In some embodiments of the present application, the organic matter includes at least one of a first organic matter, a second organic matter, a dispersant, or a wetting agent.
[0094] In some embodiments of the present application, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, and 40-70 parts of solvent. In other embodiments, the coating slurry includes 30-50 parts of inorganic particles, 2-10 parts of the first organic matter, 0.5-10 parts of the second organic matter, and 40-70 parts of solvent.
[0095] In yet other embodiments, the coating slurry includes inorganic particles, a first organic substance, a second organic substance, a dispersant, a wetting agent, and a solvent.
[0096] The present application has no particular restrictions on the type of solvent, as long as the purpose of the present application can be achieved. For example, the solvent can be selected from, but not limited to, pure water, N-methyl-2-pyrrolidone (NMP) or dimethylacetamide (DMAc). The present application has no particular restrictions on the types of wetting agents and dispersants, as long as the purpose of the present application can be achieved. For example, the wetting agent can be selected from, but not limited to, at least one of polyether-modified polysiloxane, polysiloxane, methyl acrylate polymer, dodecylphenol polyoxyethylene ether, polyoxyethylene carboxylate, polyoxyethylene alkyl ether or fatty alcohol polyvinyl ether sodium sulfate, and the dispersant can be selected from, but not limited to, at least one of polycarboxylate, ammonium polyacrylate or polyvinyl alcohol. In the present application, the number of parts refers to the number of parts by mass.
[0097] In some embodiments of the present application, when the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3L / min to 9L / min, and the temperature of the coating slurry is 18°C to 30°C. For example, the flow rate of the first organic matter can be 3L / min, 4L / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min or a range consisting of any two values therein, and the temperature of the coating slurry can be 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C or a range consisting of any two values therein. By regulating the flow rate of the first organic matter and the temperature of the coating slurry within the above range, the charge instability of the coating slurry caused by the instantaneous addition of the first organic matter can be effectively avoided, the micelle-like black spots generated in the coating after coating due to the instantaneous film formation of the first organic matter can be reduced, and the problem of uneven distribution of the first organic matter particles in the coating can be improved, which is beneficial to improving the anti-breakdown voltage capability and peeling strength of the battery separator.
[0098] In some embodiments of the present application, the pH of the coating slurry is 7 to 10, preferably 7.5 to 9.5; the viscosity of the coating slurry is 5 mPa·s to 200 mPa·s, preferably 10 mPa·s to 80 mPa·s, and more preferably 20 mPa·s to 60 mPa·s; the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm. For example, the pH of the coating slurry can be 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of them, the viscosity of the coating slurry can be 5mPa·s, 20mPa·s, 40mPa·s, 60mPa·s, 80mPa·s, 100mPa·s, 120mPa·s, 140mPa·s, 160mPa·s, 180mPa·s, 200mPa·s or a range consisting of any two of them, and the PSD of the particles in the coating slurry can be 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm or a range consisting of any two of them. The suspension stability of the coating slurry is above 95%, and the above suspension stability refers to the ratio of the suspension height to the initial liquid level height after the coating slurry is prepared and left to stand for 2 hours. By regulating the coating slurry to meet the above conditions, it is beneficial to improve the stability and uniformity of the coating slurry, so that the components of the prepared coating are evenly distributed, ensuring that the surface flatness of the coated coating is high, which is beneficial to improving the breakdown voltage resistance and peel strength of the battery separator.
[0099] In some embodiments of the present application, during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm. For example, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer can be 4.8 Hz / μm, 5.0 Hz / μm, 5.2 Hz / μm, 5.4 Hz / μm, 5.6 Hz / μm, 5.8 Hz / μm, 6 Hz / μm, or a range consisting of any two of these values. By regulating the ratio of the adsorption roller frequency to the thickness of the porous substrate layer within the above range, it can be ensured that the surface flatness of the applied coating is high and there is no foreign matter on the surface, which is beneficial to improve the anti-breakdown voltage capability and peel strength of the battery separator.
[0100] In some embodiments of the present application, the absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 20°C to 65°C. For example, the absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter can be 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, or a range consisting of any two of these values. By regulating the absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter within the above range, it is beneficial to improve the breakdown voltage resistance and peel strength of the battery separator.
[0101] In the present application, the porous substrate layer, inorganic particles, the first organic matter, the second organic matter, the dispersant, the wetting agent, etc. are all commercially available conventional substances, and the present application has no particular restrictions on their sources, as long as the purpose of the present application can be achieved. The present application can be tested in combination with the corresponding test method, and the desired porous substrate layer, inorganic particles, the first organic matter, the second organic matter, the dispersant, the wetting agent, etc. can be selected.
[0102] The third aspect of the present application provides a secondary battery, which includes the battery separator provided in the first aspect of the present application or the battery separator prepared by the preparation method provided in the second aspect. The battery separator provided in the present application has good anti-breakdown voltage capability and high peel strength, so that the secondary battery provided in the present application has good performance, such as safety performance.
[0103] The secondary battery of the present application also includes a positive electrode sheet, a negative electrode sheet and an electrolyte. The present application has no particular restrictions on the positive electrode sheet, the negative electrode sheet and the electrolyte, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0104] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. For example, the secondary battery may include, but is not limited to: lithium ion secondary battery (lithium ion battery), lithium metal secondary battery, sodium ion secondary battery (sodium ion battery), lithium polymer secondary battery, lithium ion polymer secondary battery.
[0105] Example
[0106] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0107] Test methods and equipment:
[0108] Coating surface density test
[0109] Use a 10cm×10cm mold to cut 5 square specimens of the porous substrate layer and the battery separator with coating in the transverse (TD) direction for testing. If the TD direction is less than 10cm, take 10cm in the longitudinal (MD) direction, and the specimen is not square at this time. Use an analytical balance with a measurement accuracy of 0.0001g to weigh the mass of the sample, then the surface density of the porous substrate layer = the mass of the porous substrate layer sample / (porous substrate layer sample length × porous substrate layer sample width), the coating surface density of the battery separator = the mass of the battery separator sample / (battery separator sample length × battery separator sample width), and the coating surface density of the coating = the coating surface density of the battery separator-the surface density of the porous substrate layer. Take the average value of the 5 samples as the surface density of the porous substrate layer, the coating surface density of the battery separator, and the coating surface density of the coating. The above-mentioned longitudinal direction refers to the length direction of the battery separator, and the transverse direction refers to the width direction of the battery separator.
[0110] Thickness test
[0111] The test was carried out with reference to the requirements of GB / T6672-2001 "Mechanical measurement method for thickness of plastic film and sheet".
[0112] Use a 10cm×10cm mold to cut 5 square specimens of the porous substrate layer and the battery separator with coating along the TD direction for testing. If the TD direction is less than 10cm, take 10cm in the MD direction. At this time, the specimen is not square. Use a Mahr thickness gauge (Mahr, C1202) to measure the four corners and the middle point of the specimen. The average value of the above 5 points is used as the thickness value of a single specimen. Take the average value of the test of 5 specimens as the thickness of the porous substrate layer and the thickness of the battery separator. The thickness of the coating = the thickness of the battery separator - the thickness of the porous substrate layer.
[0113] Air permeability test
[0114] The test was conducted with reference to the requirements of JIS P 8117-2009 "Paper and paperboard. Determination of air permeability and air resistance (medium range). Gurley method". A porous substrate layer and a battery separator with a coating were cut to 600mm×100mm. A Wangyan air permeability meter (ASAHI Co., Ltd., EG01-55-1MR) was used. The test time was 3s. The air permeability of the porous substrate layer and the battery separator was measured at any position every 100mm along the 600mm TD direction. The average value of the above 5 test points was recorded as the air permeability of the porous substrate layer and the battery separator. The air permeability increase of the battery separator = the air permeability of the battery separator - the air permeability of the porous substrate layer.
[0115] Particle size testing
[0116] The Dv10, Dv25, Dv50, Dv75 and Dv90 of inorganic particles were measured using a laser particle size analyzer (Dandong Better, BT-2600E), and the PSD was calculated. The specific particle size test was carried out in accordance with the national standard GB / T19077-2016 "Laser Diffraction Method for Particle Size Distribution".
[0117] Test of the mass ratio of hydroxyl groups on the surface of inorganic particles
[0118] (1) Preparation of NaCl solution: weigh 400 g of NaCl into a 2 L beaker, add 1.75 L of water to dissolve, adjust the pH to 3.0 ± 0.1 with hydrochloric acid solution, and take 150 ml of the above NaCl solution;
[0119] (2) Preparation of sodium hydroxide standard solution: c(NaOH) = 0.1 mol / L, according to GB / T 601-2016 Chapter 4 4.1 Preparation and calibration of sodium hydroxide standard titration solution;
[0120] (3) Blank sample addition: titrate with NaOH standard solution at a rate of 20 seconds / drop. When the pH value of the solution reaches 4.0±0.1, the scale value at this time is recorded as V1; continue to titrate until the pH reaches 9.0±0.1. When the pH value of the solution reaches 8.0, reduce the titration speed and add half a drop at 20 seconds. When the pH value changes less than 0.02 within 10 seconds, record the burette scale V2 and calculate the volume of sodium hydroxide solution consumed during the period from pH 4.0 to 9.0 V 空白 =V2-V1;
[0121] (4) Preparation of sample solution: Weigh the inorganic particle sample m after drying at 105°C for 2 h using an analytical balance. 样品 Put 1.5g (accurate to 1mg) in a 250ml beaker, add 150mL of sodium chloride solution, put in a stirrer and stir evenly in a magnetic stirrer, keep the temperature at 25±0.5℃ and wait for titration;
[0122] (5) Sample titration: titrate the inorganic particle sample solution at a rate of 3-4 drops per second. When the pH value reaches the end point, slow down the titration rate and record and calculate the volume V of the sodium hydroxide standard solution consumed when the solution pH changes from 4.0 to 9.0. NaOH ;
[0123] (6) Calculation of surface hydroxyl mass ratio: w(OH) = (V NaOH -V 空白 )×c(NaOH)×17.007 / (m 样品 ×1000), where V NaOH 、V 空白 The unit of is mL, the unit of c(NaOH) is mol / L, m 样品The unit is g.
[0124] Electrolyte swelling test
[0125] The first organic matter sample is placed at 105°C for drying. When the sample is dried to a constant weight (the deviation between two weighings is within 0.2g), the dried sample is weighed and the mass is recorded as M1. Then, it is placed in an electrolyte with a mass ratio of 1:1:1 of dimethyl carbonate DMC, ethyl methyl carbonate EMC, and diethyl carbonate DEC at 25°C for 24 hours. The sample is taken out, the residual electrolyte on the surface is wiped off, and the mass of the sample after soaking in the electrolyte is weighed and the mass is recorded as M2. The swelling degree of the first organic matter = (M2-M1) / M1.
[0126] Shear retention test
[0127] The first organic matter with a mass of m1 is placed in a 1000 rpm stirrer and stirred for 10 minutes, and then filtered through a 200-mesh sieve. The mass of the first organic matter remaining on the filter is m2, and the shear retention rate = m2 / m1×100%.
[0128] Peel strength test
[0129] Use a 2.5cm×30cm mold to cut the battery diaphragm sample with coating, stick the double-sided adhesive tape for peel strength test to the test plate, tear off the surface sticker of the double-sided adhesive tape, and only keep the sticker with a length of about 2cm at the end. Stick the battery diaphragm sample flatly to one end of the double-sided adhesive tape where the surface sticker is torn off, where the coating side is in contact with the double-sided adhesive tape, roll back and forth three times with a pressure roller, and then manually peel off 1cm from the coating and the porous substrate layer to make a sample strip to be tested. Clamp the end of the sample strip with residual sticker on the lower chuck of the tensile tester (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and clamp the other end of the sample strip to the upper chuck to ensure that the sample strip is not tilted. The tensile speed of the tensile tester is 50mm / min. Measure the load when the coating is peeled off from the porous substrate layer. The average value of the three measurements is taken as the peel strength between the coating and the porous substrate layer.
[0130] Breakdown voltage test
[0131] A 600mm×100mm coated battery separator was cut and an insulation tester (KIKUSUI, TOS9301) was used with the buffer time set to 10s, the test time to 10s, and the cut-off voltage to 6kV. Test points were taken at random positions every 100mm along the 600mmTD direction and the test data was recorded. The average value of the test data at the above five points was recorded as the breakdown voltage of the battery separator.
[0132] Example 1
[0133] <Preparation of coating slurry>
[0134] Carboxymethyl cellulose (density 1.02 g / cm 3 ) is dissolved in water to prepare a second organic solution with a mass concentration of 5% for standby use.
[0135] 60 parts by mass of solvent water were added to a double planetary mixer, and 35 parts by mass of inorganic boehmite particles were added and stirred evenly. Then 5.6 parts by mass of the second organic solution were added and stirred evenly, and finally 4 parts by mass of the first organic acrylic resin emulsion were added and stirred evenly to obtain a coating slurry, wherein the temperature of the slurry when the first organic was added to the coating slurry was 23.4°C, and the drip flow rate of the first organic was 6.5 L / min; the prepared coating slurry had a solid content of 35%, a pH of 8.38, a viscosity of 28.2 mPa·s, and a PSD of 0.46 μm.
[0136] The bulk density D3 of the inorganic particles in this embodiment is 0.42 g / cm 3 , true density D1 is 3.04g / cm 3 , PSD is 0.61μm, Dv50 is 0.84μm, the surface hydroxyl mass ratio is 0.04%, and the parameter conditions in the preparation process are: steam foam inlet temperature is 285.4℃, steam outlet temperature is 116℃, and steam foam time is 6min.
[0137] In this embodiment, the first organic substance is acrylic resin (density 1.15 g / cm 3 ), its swelling degree in the electrolyte is 77%, the glass transition temperature is -36.7°C, the temperature range of the glass transition temperature is 5.3°C, and the shear retention rate is 0.02%.
[0138] <Preparation of battery separator>
[0139] A polyethylene film is used as the porous substrate layer, wherein the thickness of the porous substrate layer is 7.1 μm and the surface density is 4.36 g / m 2 , air permeability is 142 s / 100cc.
[0140] The coating slurry is coated on one surface of the porous substrate layer. During the coating process, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 5.63 Hz / μm. The porous substrate layer coated with the coating slurry is dried in an oven. The absolute difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 23.3°C to obtain a battery separator. The coating thickness of the battery separator is 2.1 μm and the surface density is 7.47 g / m 2 , coating surface density is 3.11g / m 2, air permeability is 154 s / 100cc, and air permeability increase is 12 s / 100cc.
[0141] Example 2
[0142] In addition to adjusting the relevant parameters according to Table 1 and coating the porous substrate layer on both sides, the single-side coating thickness is 1.1 μm and the single-side coating surface density is 1.605 g / m 2 Other than that, the rest is the same as Example 1.
[0143] Example 3 to Example 4
[0144] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.
[0145] Example 5
[0146] In addition to adjusting the relevant parameters according to Table 1 and coating the porous substrate layer on both sides, the single-side coating thickness is 1 μm and the single-side coating surface density is 1.455 g / m 2 Other than that, the rest is the same as Example 1.
[0147] Comparative Examples 1 to 5
[0148] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.
[0149] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0150] Table 1
[0151]
[0152] Note: The "amount fraction" in Table 1 refers to the mass fraction of each substance (including the solvent of each substance) in the coating slurry, the "solid amount fraction" refers to the mass fraction of each substance (excluding the solvent of each substance) in the coating slurry, the "coating proportion" refers to the mass proportion of each substance (excluding the solvent of each substance) in the prepared coating, and the "slurry proportion" refers to the mass proportion of each substance (including the solvent of each substance) in the coating slurry.
[0153] It can be seen from Examples 1 to 5 and Comparative Examples 1 to 5 that the present invention regulates the battery separator The value of is within the range of this application, the battery separator has a large breakdown voltage and high peel strength, and has good anti-breakdown voltage capability. The value of is not within the scope of the present application, and the breakdown voltage and peel strength of the battery separator are small, indicating that the battery separator has poor anti-breakdown voltage capability.
[0154] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0155] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0156] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A battery separator, comprising a porous substrate layer and a coating disposed on at least one surface of the porous substrate layer, wherein the coating comprises inorganic particles and organic matter, The coating surface density of the coating is C g / m 2 , the thickness of the coating is H μm, the air permeability increase of the battery separator is P s / 100cc, and the true density of the inorganic particles is D1g / cm 3 , the density of the organic matter is D 2i g / cm 3 Based on the mass of the coating, the mass percentage of the inorganic particles is W1, and the mass percentage of the organic matter is W 2i ,satisfy: ,in, , n is the number of types of the organic matter; the mass percentage of the inorganic particles satisfies: 82%≤W1≤97%, and the mass percentage of the organic matter satisfies: ; The bulk density of the inorganic particles is D3 g / cm 3 , the inorganic particles satisfy: 2.3≤D1-D3≤3.1; The peel strength between the coating layer and the porous substrate layer is ≥20 gf / 15 mm, and the breakdown voltage of the battery separator is ≥0.5 kV.
2. The battery separator according to claim 1, wherein The thickness of the coating satisfies: 0.5≤H≤8, and the coating surface density of the coating satisfies: 1≤C≤10.
3. The battery separator according to claim 1, wherein The particle size distribution PSD of the inorganic particles satisfies: 0.38 μm ≤ PSD ≤ 0.63 μm, wherein, 。 4. The battery separator according to claim 1, wherein The surface hydroxyl groups of the inorganic particles account for 0 to 0.06% by mass.
5. The battery separator according to claim 1, wherein The inorganic particles are selected from at least one of silicon dioxide, aluminum oxide, magnesium oxide, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, barium fluoride or barium titanate.
6. The battery separator according to claim 1, wherein The organic matter comprises a first organic matter, and the first organic matter is selected from at least one of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers or acrylamide and its derivative copolymers, Based on the mass of the coating, the mass percentage of the first organic matter is W 21 , which satisfies: 3%≤W 21 ≤10%.
7. The battery separator according to claim 6, wherein: The first organic matter satisfies at least one of the following characteristics: (1) The swelling degree of the first organic matter in the electrolyte is 40% to 150%; (2) The glass transition temperature of the first organic substance is between -40°C and 100°C, and the temperature range of the glass transition temperature is ≤12°C, wherein the temperature range of the glass transition temperature is the difference between the end point and the start point of the glass transition temperature; (3) The shear retention rate of the first organic matter is 0 to 0.08%.
8. A method for preparing a battery separator according to any one of claims 1 to 7, comprising the following steps: (1) providing a porous substrate layer; (2) providing a coating slurry including inorganic particles and organic matter, wherein the organic matter includes a first organic matter; (3) The coating slurry is coated on at least one surface of the porous substrate layer, and dried to obtain a battery separator including the coating layer.
9. The preparation method according to claim 8, which satisfies at least one of the following characteristics: (1) The coating slurry comprises 30-50 parts of inorganic particles, 2-10 parts of a first organic matter and 40-70 parts of a solvent; (2) When the first organic matter is added to the coating slurry, the flow rate of the first organic matter is 3 L / min to 9 L / min, and the temperature of the coating slurry is 18° C. to 30° C.; (3) The pH of the coating slurry is 7 to 10, the viscosity is 5 mPa·s to 200 mPa·s, and the PSD of the particles in the coating slurry is 0.25 μm to 0.5 μm; (4) during the coating process of the coating slurry, the ratio of the adsorption roller frequency to the thickness of the porous substrate layer is 4.8 Hz / μm to 6 Hz / μm; (5) The absolute value difference between the oven temperature of the drying process and the glass transition temperature of the first organic matter is 20° C. to 65° C. 10 . A secondary battery comprising the battery separator according to claim 1 or the battery separator prepared by the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Separator for electrochemical device and electrochemical device comprising same
CN117730454A
Lithium battery diaphragm, coating slurry, and preparation method and application of coating slurry
CN118867581A